As prestações extracontratuais e a manutenção do equilíbrio econômico-financeiro dos contratos de obras públicas - Negrini Neto, João (2018)
During the execution of a public works contract, it is very common for the contractor to encounter inaccuracies in the projects franchised by the administration or unforeseeable circumstances that require adaptation of the contracting scope. There are situations, even in which the contractor is led to execute these non-contractual installments, regardless of the inclusion in the scope of the contract by means of a previous addition. In this study, we identified how the legal system deals with this issue in the face of the constitutional duty to maintain the economic-financial balance of administrative contracts. We deal with the aspects related to the general theory of private contracts and the specifics involved in the legal regime of administrative contracts for public works. We delimit the scope of subsidiarity from the application of the former in reaction to the latter. We evaluate the theory of unilateral acts, especially business management and unjust enrichment. In the end, we rehearse the application of the theory of unilateral acts to public works contracts as a basis to guarantee the fair remuneration of the services executed at the risk of the particular in the context of these contracts, without previous modification contractual